THE RELEVANCE OF RONALD DWORKIN'S THEORY FOR CREATING AGRARIAN JUSTICE IN INDONESIA - Muh. Afif Mahfud (Yustisia Jurnal Hukum, 2019)
Law enforcement related to Agraria is unjustly marked by the discrepancy of natural resources ownership and many agrarian conflicts. This is normative research, use conceptual approach and secondary data. Then, data collected is analyzed qualitatively. Based on research, moral reading stated by Dworkin is very relevant to be implemented to create agrarian justice in Indonesia because of its endorse rule to be interpreted according to the justice principle. Dworkin's theory of justice is very relevant in creating justice in Indonesia because of : (1) emphasize the importance of public participation and individual understanding in constructing justice; (2) acknowledgment of public diversity; and (3) giving attention to disadvantaged people.